Streamlining induction of labour (IOL) pathway using Bolton improving care system (BICS) at royal Bolton hospital (RBH). (18th April 2012) - Wong, S; Moss, R; Tomlinson, AJ; Katakam, N
Abstract : Objective: To review the IOL pathway by a multi-disciplinary team in March 2011 using BICS as the number of IOLs was anticipated to increase from 900 to 1500 due to merging with 2 neighbouring units. Findings: Inconsistency in practice in offering membrane sweep Inconsistency in dates for IOL for postdates No information leaflet for IOL Difficult to obtain slot in IOL dairy (6 spaces on weekdays and 2 on weekend) Delays in prescription of Propess Actions: Offer membrane sweeps to nulliparous women at 40 weeks and to all women at 41 weeks (NICE recommendation) IOL for postdates ≥ term + 11 days Design IOL leaflet Update IOL guideline Check IOL diary daily to free slots by removing delivered women Patient Group Directive for Propess for midwives Conclusion: There was improvement in the IOL pathway with decreased delays and more spaces in IOL dairy. There was decrease in % of IOL for postdates, increase in membrane sweeps offered and increase in IOL after ≥ term + 11. However, there was decrease in vaginal delivery, instrumental delivery rate and increase in section rate.